40th Winter School on Wave and Quantum Acoustics Szczyrk, Poland, February 27 – March 4, 2011 - BUKOWSKI, Roman (Archives of Acoustics, 2011)
I have a great pleasure to inform the “AA” Readers that the 40th Winter School on Wave and Quantum Acoustics, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics – Scientific-Didactics Center at Silesian University of Technology, is planned at the turn of February and March 2011 in beautiful scenery of Silesian Beskidy Mountains. Many times it was organized in Wisła, Skoczów, Szczyrk and Korbielów, and this year it will be organized again in Szczyrk. As always, the School has been a place where achievements of various sections of physical acoustics (especially molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, acoustoelectronics, photoacoustics, acoustics of solids etc.) are being exchanged. Moreover, some similar and related topics, for example optoelectronics and thermal wave methods, will be presented too. As at the previous years, the School will be divided into three different, but complementary, parts – Winter Workshops (WW). Chronologically it will be: 7th WW on Acoustoelectronics (chairman Prof. Marian Urbanczyk, Silesian University of Technology, Gliwice), 7th WW on Molecular Acoustics, Relaxation and Calorimetric Methods (chairwoman Dr. Marzena Dzida, Silesian University, Katowice) and 16th WW on Photoacoustics and Thermal Waves Methods (chairman Prof. Jerzy Bodzenta, Silesian University of Technology, Gliwice). Moreover, this year we propose to participate in associated conference – the 5th Conference on Integrated Optics – Sensors, Sensing Structures and Methods (chairman Prof. Tadeusz Pustelny, Silesian University of Technology, Gliwice).